On the taxonomic composition and phylogenetic affinities of the recently proposed clade Vegaviidae Agnolín et al., 2017 ‒ neornithine birds from the Upper Cretaceous of the Southern Hemisphere. (June 2018) - Mayr, Gerald; De Pietri, Vanesa L.; Scofield, R. Paul; Worthy, Trevor H.
Abstract: Polarornis and Vegavis from the Upper Cretaceous of Antarctica are among the few Mesozoic birds from the Southern Hemisphere. In the original descriptions, they were assigned to two widely disparate avian clades, that is, Gaviiformes and crown group Anseriformes, respectively. In a recent publication, however, specimens referred to both taxa were classified into a new higher-level taxon, Vegaviidae, to which various other late Mesozoic and early Cenozoic avian taxa were also assigned. Here, we detail that classification into Vegaviidae is poorly supported for most of these latter fossils, which is particularly true for Australornis lovei and an unnamed phaethontiform fossil from the Waipara Greensand in New Zealand. Plesiomorphic traits of the pterygoid and the mandible clearly show that Vegavis is not a representative of crown group Anseriformes, and we furthermore point out that even anseriform or galloanserine affinities of Vegaviidae have not been firmly established. Highlights: The recently proposed taxon Vegaviidae includes Vegavis and Polarornis from the Upper Cretaceous of the Southern Hemisphere. Australornis and an unnamed phaethontiform from the lower Paleocene of New Zealand were incorrectly referred to Vegaviidae. Neither anseriform nor galloanserine affinities of Vegaviidae have been firmly established.